Shear interfacial fracture of strain-hardening fiber-reinforced cementitious composites and concrete: A novel approach. (August 2021) - Li, Qing-Hua; Yin, Xing; Huang, Bo-Tao; Luo, Ai-Min; Lyu, Yao; Sun, Chao-Jie; Xu, Shi-Lang
Highlights: A novel approach for shear interfacial fracture of concrete was proposed. Stress intensity factor of bi-material double-edge specimen was analytically obtained. K IIc of strain-hardening cementitious composites and concrete was obtained. DIC was used to understand the interface shear behavior of cement-based materials. Abstract: For strengthening and repair of concrete structures, shear interfacial behavior between concrete substrate and strengthening materials (e.g., strain-hardening fiber-reinforced cementitious composites) is critical for the structural performance of concrete members. In this study, a novel approach for shear interfacial fracture of cement-based materials was proposed to achieve pure shear failure. The stress intensity factor of the bi-material double-edge notched specimen was analytically obtained for the first time. A numerical investigation was carried out to confirm the suitability of the proposed approach. Then, shear interfacial fracture tests between strain-hardening cementitious composites and ordinary concrete were conducted to demonstrate its feasibility and to determine the shear interfacial fracture toughness. Additionally, digital image correlation (DIC) technique was used to analyze the shear behavior of the bi-material interface. The proposed approach can be applied to evaluate shear interfacial behaviors of cement-based materials.